2009
DOI: 10.1029/2009gl037786
|View full text |Cite
|
Sign up to set email alerts
|

Southern Australian rainfall and the subtropical ridge: Variations, interrelationships, and trends

Abstract: Monthly values of the latitude and intensity (mean maximum pressure) of the subtropical ridge (STR), averaged across Australian longitudes (105–155°E), have been related to variations and trends in rainfall over southern Australia (south of 30°S), for 1958–2005. There is an abrupt shift of latitude of the subtropical ridge over Australia at the onset of winter. In the cooler part of the year the intensity of the STR is more closely related to rainfall variations (and correlations between latitude and rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 13 publications
(14 reference statements)
5
75
0
Order By: Relevance
“…Therefore, these results support previous work (e.g. Drosdowsky, 2005;Timbal et al, 2007;Larsen and Nicholls, 2009;Williams and Stone, 2009) suggesting that the "post-1993 autumn rainfall decline" can be attributed to a strengthening and southward movement of the STR during autumn and a reduction in the frequency of rain producing troughs.…”
Section: What Is Causing the Decrease In Autumn Rainfall?supporting
confidence: 91%
“…Therefore, these results support previous work (e.g. Drosdowsky, 2005;Timbal et al, 2007;Larsen and Nicholls, 2009;Williams and Stone, 2009) suggesting that the "post-1993 autumn rainfall decline" can be attributed to a strengthening and southward movement of the STR during autumn and a reduction in the frequency of rain producing troughs.…”
Section: What Is Causing the Decrease In Autumn Rainfall?supporting
confidence: 91%
“…The STR provides a measure of the high pressure systems that typically lie to the north of the storm tracks and therefore have a role in steering the storm track and the fronts embedded in the westerly flow. The intensity, position and other characteristics of the STR are linked to the frequency and strength of storms and fronts that cross southern Australia, and the STR is therefore an important feature of Australian rainfall variability and change (Pittock 1971;Pittock 1973;Drosdowsky 2005;Larsen and Nicholls 2009;Williams and Stone 2009;Timbal et al 2010;Timbal and Drosdowsky 2013;Whan et al 2013). Both the STR-I and STR-P are negatively correlated with rainfall anomalies in southern Australia on an inter-annual timeframe (Figures 1b and 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have analysed the contribution of di fferent external forcing mechanisms (Timbal, Arblaster, and Power 2006;Narisma and Pitman 2003;Rotstayn et al, 2009) to the observed rainfall changes in different parts of Australia. In addition, the influence of proximate causes of Australian rainfall variability has been intensively studied and linkages with major atmospheric and oceanic modes of variability such as the Southern Annular Mode or the El Niño-Southern Oscillation have been documented (Risbey et al, 2009;Nicholls 2010;Larsen and Nicholls 2009;Frederiksen et al, 2010;Smith and Timbal 2012;Cai and Cowan 2012). These studies into proximate drivers imply that a considerable fraction of recent rainfall variability and trends is due to natural internal variability rather than externally forced.…”
Section: Introductionmentioning
confidence: 99%